Quality of life of older women living with HIV: comparative assessment of physical and mental health-related markers using a large Canadian Sexual and Reproductive Health Cohort Study. Issue 2 (26th April 2019) - Kteily-Hawa, Roula; Andany, Nisha; Wang, Ying; Logie, Carmen H.; Tharao, Wangari; Conway, Tracey; Webster, Kath; de Pokomandy, Alexandra; Kaida, Angela; Hogg, Robert; Loutfy, Mona; ,
Abstract: Objective : This study assessed and compared physical and mental health components of quality of life (QoL) for older and younger women living with HIV (WLWH). Method : Using survey data from the Canadian HIV Women's Sexual and Reproductive Health Cohort Study, demographic, well-being, and physical and mental health-related QoL (HR-QoL) variables were compared between older (≥50 years) and younger (<50 years) WLWH. As the only significantly different QoL component, bivariate analyses and linear regression were used to assess factors associated with physical HR-QoL of older women. Results : The sample frame comprised 1, 422 women (28.0% older women). Younger WLWH's mean age was 37.8 years (SD = 7.4) compared to older WLWH (55.8 years, SD = 5.3). Compared to younger WLWH, older WLWH had poorer physical HR-QoL (40.0 vs. 50.7; p  < 0.001) but similar mental HR-QoL (42.7 vs. 42.1; p  > 0.001). Older WLWH had lower social support ( p  < 0.001) with no significant differences in depressive symptoms or resilience. Resilience was associated with improved physical HR-QOL. Food insecurity, poorer mental HR-QoL and depressive symptoms were associated with poorer physical health. Discussion: Compared to younger WLWH, older WLWH had poorer physical HR-QoL, which was associated with resilience, food insecurity and mental health factors, highlighting the complex interactions of health-related social-ecological factors impacting aging WLWH.